(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: The digitalization of general dentistry has significantly impacted numerous factors, including clinical considerations, student training, treatment options, patient motivation, laboratory procedures, practice administration, and dental research. As the popularity of 3D printing and Computer Aided. Designing/Computer Aided Manufacturing (CAD/CAM) technology has increased recently, obtaining dental students' and dentists' knowledge, and attitudes towards artificial intelligence in dentistry was important. Objective: The study aimed to assess the knowledge and awareness of digital dentistry among dentists, dental interns, and dental students in Saudi Arabia. Methods: This study is a cross-sectional questionnaire survey in Saudi Arabia between July 2024 to November 2024. The study was recruit participants through an online survey. The inclusion criteria for this study were as follows: undergraduate dental students, dental interns, and dentists in Saudi Arabia and non-dental professionals were excluded from this study. Results: The study results revealed varying levels of knowledge, awareness, and perception regarding digital dentistry. While 54% identified prosthodontics as the main field utilizing CAD/CAM technology, and a significant 77.7% recognized its effectiveness in fabricating various restorations, 57.1% exhibited a low overall knowledge of digital dentistry. Furthermore, though 50.7% reported using digital devices, satisfaction with CAD/CAM restorations was low, with only 27.5% expressing high satisfaction. A substantial majority (82.9%) advocated for increased educational emphasis on digital dentistry, and 90.5% wished to incorporate CAD/CAM technology into their practices. Conclusion: Despite widespread recognition of the benefits of CAD/CAM technology and a strong desire to incorporate digital methods into practice, a significant portion of respondents demonstrated low knowledge levels and limited practical experience. High costs, inadequate training, and lingering reliance on traditional methods were identified as barriers to the effective implementation of digital dentistry.